Les « frontaliers » de la coopération entre Marseille et Alger : de la marge à la médiation - Chérif Dris (L’Année du Maghreb)
Co-operation between the city of Marseille and the wilaya of Algiers cannot be apprehended merely as a legal and institutional phenomenon. Co-operation is above all a public act in which a variety of social actors play an important part. Among the social actors, French-born Algerians (pieds-noirs and second generation immigrants) as well as Algerian expatriates are among the structural elements of this of the co-operative effort. Placed at the vanguard of Franco-Algerian relations by accident of geography and history, these actors play a double role while occupying the high-ground in this co-operative space. As actors they are at once passive, dependent for action upon a rationale with international and local objectives, and active actors as intermediaries in a cooperative process where the exchange of resources is a structuring element.